Research into the process of mechanical formation of the upper part of a raw cotton bundle - Sailov, Rahib Aqaqul; Veliev, Fazil Ali; Kerimov, Qusni Kadir (Eastern-European Journal of Enterprise Technologies, 2017)
The process of formation of the upper part of a raw cotton bundle was examined. We proposed a method for kinematic analysis of mechanisms of the cotton-processing machines, including a mechanical bundling press, and developed an algorithm for its computer implementation. The proposed method makes it possible to obtain equations for determining the kinematic parameters of a mechanism for the formation of the upper part of a cotton bundle at the assigned law of the motion of a drive link, which is the cam. We experimentally studied the possibility of forming the upper part of a bundle with the required density of cotton, which ensures stability of the formed bundle. Taking into account the influence of density of raw cotton in the bundle on the adhesion between waste and cotton, and based on the impact of this on the cleaning effect, we conducted theoretical and experimental research. The study performed allowed us to determine the density of raw cotton in a bundle depending on the time and height of the bundle, and to investigate the influence of waste adhesion on the ginning effect.